Taklif and the Fulfillment of the Rights of Persons with Mental and Intellectual Disabilities: An Islamic Legal Perspective - Fuad Masykur; Ahmad Bahrul Hikam; Muhammad Amin (Hukum Keluarga Islam IAIN LANGSA, 2025)
It's so important to recognize that people with disabilities are an integral part of our multicultural society. As a Muslim community, they also have rights and obligations like other Muslim communities. However, there is still so much to be done to gain a more comprehensive understanding of taklif studies regarding legal construction for people with disabilities. This research is an exciting step forward in constructing the taklif of persons with disabilities in their capacity as legal subjects. This research uses qualitative literature methods, with the main data being the Koran and legal hadith. Secondary data is obtained through legal commentary books, articles, and others. A normative approach is used in this research to look at the legal aspect of the meaning of legal sources that are directly related to taklif for people with disabilities. This approach was also carried out to find out more about the position of taklîf for people with mental and intellectual disabilities and the influence of mental and intellectual disabilities on Ahliyyah. The findings indicate that individuals with psychosocial and complex mental disorders are not inherently affected by taklîf in terms of taklîf and Ahliyyah. Another form of disabled individual is the mukallaf, who are subject to taklîf obligations based on their skills. With regard to the right to practice religion, people with mental and intellectual disabilities can still complete zakat responsibilities as a guardian pays them. Individuals with mental and intellectual disabilities are prohibited from exploiting their assets, regardless of whether their condition is permanent or temporary. Consequently, they are subject to a guardianship system. With regard to marriage, those with modest mental and intellectual disabilities who have an ahliyah wujub and an ahliyah ada' kamilah are considered to have a lawful marriage status. Conversely, if the disability is moderate or severe and there is a need to marry, the marriage may be performed by a wali mujbir.